2009
DOI: 10.2166/wst.2009.690
|View full text |Cite
|
Sign up to set email alerts
|

Photo-degradation of clofibric acid by ultraviolet light irradiation at 185 nm

Abstract: As a metabolite of lipid regulators, clofibric acid (CA) was investigated in this study for its ultraviolet (UV) degradation at monochromatic wavelength of 185 nm using Milli-Q water and sewage treatment plant (STP) effluent. The effects of CA initial concentration, solution pH, humic acid (HA), nitrate and bicarbonate anions on CA degradation performances were evaluated. All CA degradation patterns well fitted the pseudo-first-order kinetic model. The results showed that OH generated from water photolysis by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The considerable difference in the rate constants with varying initial pH might be due to the change in the reaction species of CA. The p K a value of CA was 3.18, 50 and its species distribution is shown in Fig. 4 .…”
Section: Resultsmentioning
confidence: 95%
“…The considerable difference in the rate constants with varying initial pH might be due to the change in the reaction species of CA. The p K a value of CA was 3.18, 50 and its species distribution is shown in Fig. 4 .…”
Section: Resultsmentioning
confidence: 95%
“…Current traditional wastewater and drinking water treatment processes, such as coagulation, sedimentation and filtration, and biological processes, do not efficiently remove CA [ 8 ]. It was reported that ultraviolet (UV) photolysis could efficiently degrade CA in wastewater [ 9 ]. Generally, UV photolysis is used as the disinfection process in wastewater treatment plant [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Direct VUV photolysis of water can produce an appreciable amount of • OH for oxidative decomposition of organic pollutants without any additional power input. As a result, the VUV/UV process has been applied to enhance the disinfection of pathogens and the removal of dissolved organic matter and various micropollutants in water and wastewater. For UV-based AOPs (e.g., UV/chlorine), if a VUV/UV LP lamp (using synthetic quartz) is used as the light source, a higher efficiency can be expected than for a conventional UV LP lamp.…”
Section: Introductionmentioning
confidence: 99%